If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 9(2) = 3y Multiply 9 * 2 -6 + 18 = 3y Combine like terms: -6 + 18 = 12 12 = 3y Solving 12 = 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 12 + -3y = 3y + -3y Combine like terms: 3y + -3y = 0 12 + -3y = 0 Add '-12' to each side of the equation. 12 + -12 + -3y = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -3y = 0 + -12 -3y = 0 + -12 Combine like terms: 0 + -12 = -12 -3y = -12 Divide each side by '-3'. y = 4 Simplifying y = 4
| 204+10h=20h+14 | | f(60)=x+50 | | 6R+1=28 | | -6+9(0)=3y | | 2x+xX=4 | | 2x-10=24-9x | | -4x+2(3)=12 | | f(x)=x+50 | | b^2+27b-180=0 | | y+4=-8(x+8) | | 6-2y= | | 5(x-7)=-20 | | -4x+14y=-67 | | 5e+6=22 | | 3+5+[-4]+x=10 | | 5r^2+100=45r | | 3(-2)-2y=-8 | | -12=6r | | 13-5m=4-5m | | 3(0)-2y=-8 | | 6/11x=12 | | 10=p/9 | | X(3x+6)=12 | | 2(4-12)+3a=6a+1 | | 20x+45y= | | 3(2)-2y=-8 | | 2m+r=p | | 4B+5=18 | | x=-8+y | | 5x+18x+2+15x+22x-2=360 | | 16+90n=35n-50 | | 3B+-4=26 |